A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran - Perreau, Michel; Ghahari, Hassan; Angelini, Fernando (Zootaxa, 2017)
This paper gives an overview of the fauna of Iranian Leiodidae (Coleoptera: Staphylinoidea). Altogether 59 species from 20 genera and 3 subfamilies (Cholevinae, Leiodinae and Platypsyllinae) are listed. Synonymies and distribution data are given. Choleva (Choleva) uludagica Giachino & Vailati, 2000 is newly recorded from Iran. Catops kyrbyi collaris Szymczakowski, 1976 is synonymized with Catops kirbyi kirbyi Spence, 1815.